Mukim as a Customary Law Community in Customary Forest Management in Aceh Besar - Sriwahyuni, Yenny; Mumtazinur, Mumtazinur; Kesuma, Aulia (Faculty of Sharia and Law, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
Customary forests are forests that are located within the area of a Customary Law Community. In theory, only people who live in forest areas are able to maintain forest areas well because they have a reciprocal relationship that cannot be separated. These communities are often referred to as indigenous communities or customary law communities. Aceh Besar has a very large forest area, there are three forest areas that have been categorized as customary forest areas with three customary law communities that are included in the indicative customary forest map of the Indonesian Ministry of Environment and Forestry. This research examines: Efforts that can be made by customary law communities in Aceh Besar to obtain their rights to customary forests and how optimizing customary forest management can provide protection to customary law communities and customary forest areas in Aceh Besar. The results of the research show that currently three customary forest areas in Aceh Besar have been removed from the indicative customary forest map, this is because during the verification period the customary law communities (Mukim) files were unable to provide evidence in the form of regional regulations in Aceh Besar which designated them as customary law communities recognized in accordance with the requirements. in the Minister of Environment and Forestry's regulations, so that the three mukims in Aceh Besar do not have legal rights to manage customary forests. Optimizing protection for forest areas and Mukim in Aceh Besar is also not going well.